2021
DOI: 10.1002/jha2.228
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt from COVID‐19 coagulopathy

Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has already left an indelible mark in human lives. Despite the havoc it created, this pandemic also saw significant advances in the management of an infectious disease wherein worldwide collaborative efforts from health care professionals have been unprecedented. One of the commonest complications recognised early in the pandemic is the development of coagulopathy. In this review, the lessons learnt from COVID‐19 coagulopathy are summarised with some perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Coagulopathies [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102], and especially the formation of extensive microclots in vivo, are a hallmark of both COVID [85,[103][104][105][106][107][108][109][110][111][112][113][114][115] and long COVID [116,117], and we have demonstrated that these microclots too are amyloid in character [108,109,116]. Importantly, the addition of purified, recombinant SARS-CoV-2 S1 spike protein to coagulation-competent normal plasma is sufficient to induce the formation of anomalous clots [118] that adopt amyloid states that are also resistant to fibrinolysis [108].…”
Section: Amyloid Fibrin Microclots (Fibrinaloids) In Covid-19 and Lon...mentioning
confidence: 67%
“…Coagulopathies [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102], and especially the formation of extensive microclots in vivo, are a hallmark of both COVID [85,[103][104][105][106][107][108][109][110][111][112][113][114][115] and long COVID [116,117], and we have demonstrated that these microclots too are amyloid in character [108,109,116]. Importantly, the addition of purified, recombinant SARS-CoV-2 S1 spike protein to coagulation-competent normal plasma is sufficient to induce the formation of anomalous clots [118] that adopt amyloid states that are also resistant to fibrinolysis [108].…”
Section: Amyloid Fibrin Microclots (Fibrinaloids) In Covid-19 and Lon...mentioning
confidence: 67%
“…12-14 All the patients had elevated D-dimer and CRP but these alone cannot be used as an indicator toward a higher propensity for coagulopathy. 15…”
Section: Discussionmentioning
confidence: 99%
“…The epiphenomenon was likely a secondary event following endothelial cell and platelet protein damage. This epiphenomenon is one of the lessons we have learned from COVID-19 sepsis [53]. In retrospect, some of the vaccinated individuals had ITP-like syndrome and CVST was formed as venous combined micro-macrothrombosis following additional cerebral venous sinus injury [54].…”
Section: Molecular Evidence Of Venous Endotheliopathymentioning
confidence: 97%